EXAMINING CHEMISTRY TECAHRS' REFLECTIVE JOURNALS DURING MENTORING PRACTİCES - Ayşegül SAĞLAM ARSLAN; Canan Cengiz; Faik Özgür Karatas; Suat Ünal (Borys Grinchenko Kyiv Metropolitan University, 2023)
The aim of this study is to determine the impact of mentorship program on professional development of the mentees. This study is guided by case study. The case, in this study, is each of four chemistry teachers who took part in mentorship program as mentees in order to better understand the mentorship program. The data collection tool employed in this study is the reflective journals kept by the mentees throughout the mentorship practice (for eight weeks). Participants filled out reflective journals for evaluation after they completed the lessons (material, lesson plan, etc.) they prepared in the group mentoring sessions held every week. These forms have five questions that might lead mentees to reflect on their implementation of the plans and their professional development in the course of the mentorship program. The data obtained suggest that the mentees had qualified reflections on their current practices as well as future practices. The mentors frequently noted in their weekly reflective journals form that the mentorship program has a positive impact on their teaching methods competencies while implementing the co-designed lessons plans. On the other hand, the most important problem that the mentees uttered is the need for extra time as they could not complete the activities within the planned time frame. In light of the findings, it can be deduced that the mentorship program has improved the professional practices of the mentees.